Nitric oxide in the insular cortex modulates baroreflex responses in a cGMP-independent pathway - Ferreira-Junior, Nilson C.; Crestani, Carlos C. [UNESP]; Lagatta, Davi C.; Resstel, Leonardo B.M.; Correa, Fernando M.A.; Alves, Fernando H.F. (Elsevier, 2020)
Insular cortex is a brain structure involved in the modulation of autonomic activity and cardiovascular function. The nitric oxide/cyclic guanosine-3′,5′-monophosphate pathway is a prominent signaling mechanism in the central nervous system, controlling behavioral and physiological responses. Nevertheless, despite evidence regarding the presence of nitric oxide-synthesizing neurons in the insular cortex, its role in the control of autonomic and cardiovascular function has never been reported. Thus, the present study aimed to investigate the involvement of nitric oxide/cyclic guanosine-3′,5′-monophosphate pathway mediated by neuronal nitric oxide synthase (nNOS) activation within the insular cortex in the modulation of baroreflex responses in unanesthetized rats. For this, we evaluated the effect of bilateral microinjection of either the nitric oxide scavenger carboxy-PTIO, the selective neuronal nitric oxide synthase inhibitor Nω-Propyl-L-arginine or the soluble guanylate cyclase inhibitor ODQ into the insular cortex on the bradycardia evoked by blood pressure increases in response to intravenous infusion of phenylephrine, and the tachycardia caused by blood pressure decreases evoked by intravenous infusion of sodium nitroprusside. Bilateral microinjection of either NPLA or carboxy-PTIO into the insular cortex increased the reflex bradycardic response, whereas the reflex tachycardia was decreased by these treatments. Bilateral microinjection of the soluble guanylate cyclase inhibitor into the insular cortex did not affect any parameter of baroreflex function evaluated. Overall, our findings provide evidence that insular cortex nitrergic signaling, acting via neuronal nitric oxide synthase, plays a prominent role in control of baroreflex function. However, control of reflex responses seems to be independent of soluble guanylate cyclase activation.
Keywords: Baroreflex; GMPc; Insular cortex; Nitric oxide